Les livres des gens à Damas vers 1700 - Colette Establet; Jean-Paul Pascual (Revue des Mondes Musulmans et de la Méditerranée)
This work is based upon the study of 450 probate inventories which were inscribed in two registers in Damascus (1686-1717) under the authority of the qassam 'arab judge. This judge's role consisted of apportioning out the legal share of successions (mukhallafa, tarika) for civilians, both men and women, amongst their diverse heirs or, on the other hand, attributing their entire inheritance to the state's treasury which was, indeed, the case in several instances studied. The documents are drawn up according to a relatively homogenous pattern : the preambule gives the deceased's name and tides as well as sometimes noting his profession (which can often be guessed in relation to the types of properties that he possessed) and his place of residence and work. In the second part, the qadi and his scribes give a detailed list of the deceased's assets, his moveable property and his real-estate in addition to any outstanding credit. The third part notes the liabilities in the succession and the final section gives the net amount of the inheritance to be shared among the heirs.In his meticulous description of the deceased's assets, the judge mentions the presence of books if he comes upon them. The article evaluates the number of Damascene homes which contain books, who owns them, which types of books are possessed –information available according to whether the scribe wrote down the titles. One never knows, however, whether the books were read.